2023
DOI: 10.1186/s12879-023-08619-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization strategy for the early timing of bronchoalveolar lavage treatment for children with severe mycoplasma pneumoniae pneumonia

Xiangtao Wu,
Weihong Lu,
Tuanjie Wang
et al.

Abstract: Background Early evaluation of severe mycoplasma pneumoniae pneumonia (SMPP) and the prompt utilization of fiberoptic bronchoscopic manipulation can effectively alleviate complications and restrict the progression of sequelae. This study aim to establish a nomogram forecasting model for SMPP in children and explore an optimal early therapeutic bronchoalveolar lavage (TBAL) treatment strategy. Methods This retrospective study included children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Mycoplasma pneumoniae pneumonia (MPP) is notably prevalent in paediatric wards, accounting for approximately 10–40% of paediatric community-acquired pneumonia pathogens [ 1 ]. This condition can cause not only respiratory tract infections but also lead to extrapulmonary manifestations, such as myocardial damage, Stevens–Johnson syndrome, encephalitis, and liver damage [ 2 , 3 ]. More concerning is that mycoplasma pneumoniae (MP) can result in refractory mycoplasma pneumoniae pneumonia (RMPP).…”
Section: Introductionmentioning
confidence: 99%
“…Mycoplasma pneumoniae pneumonia (MPP) is notably prevalent in paediatric wards, accounting for approximately 10–40% of paediatric community-acquired pneumonia pathogens [ 1 ]. This condition can cause not only respiratory tract infections but also lead to extrapulmonary manifestations, such as myocardial damage, Stevens–Johnson syndrome, encephalitis, and liver damage [ 2 , 3 ]. More concerning is that mycoplasma pneumoniae (MP) can result in refractory mycoplasma pneumoniae pneumonia (RMPP).…”
Section: Introductionmentioning
confidence: 99%
“…Some children with solid lung lesions and bronchial plastination were treated with beroptic bronchoscopy; however, the microscopic diagnosis rates did not differ signi cantly between the two groups (Table 4). Wu et al showed that timely beroptic bronchoscopy is effective in reducing complications and sequelae [17]. Early re nement of beroptic bronchoscopy and the removal of bronchial plastination are effective treatment options [18].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of SMPP has been increasing in China over the past decade [ 11 ]. Early assessment of SMPP and timely application of bronchoscopy can effectively alleviate complications and limit sequelae progression [ 12 ]. FOB and BAL can rapidly detect pathogens and identify drug-resistance genes, which are conducive to the precise treatment of severe infections [ 3 ] and reduce the irrational use of antibiotics [ 10 ].…”
Section: Discussionmentioning
confidence: 99%